PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING DENGAN MEDIA SMALL-SCALE CHEMISTRY UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA PADA KELAS XI IPA SMAN 1 TALUN - Istiqomah, Istiqomah (Jurnal Pendidikan Sosiologi dan Humaniora, 2022)
The concept of learning will be successful if students are actively involved in the learning process so that students not only accept ideas from the teacher but also participate in finding concepts. One of the efforts to find these concepts is the Discovery learning method carried out in the laboratory with Small Scale Chemistry media. This study aimed to determine whether the application of learning with the Discovery learning model with Small Scale Chemistry media on acid-base materials could increase the activity and learning outcomes of chemistry class XI science. This research is a classroom action research with two cycles. The subjects of this study were students of class XI IPA-3 even semester with a total of 36 students. This study found an increase in learning activities and student learning outcomes in learning chemistry on acid-base material by applying the Discovery learning model using Small Scale Chemistry media. This is evidenced by the average student learning outcomes completed: the first cycle is 69.4%, and the second cycle is 86%. While the moderate student activity in the first cycle reached 77% and the second cycle was 86.0%. And the average teacher activity in the first cycle is 77.7%, while the second cycle is 88.15%.